“Ratapan di Negeri Asing”: Mazmur 137 dan Para Pekerja Migran Indonesia di Malaysia dan Brunei Darussalam - Dwi Budhi Cahyono (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Abstract. This article is a study of Psalm 137 with the aim of providing a basis for reflection for us to understand the Psalm of lamentation as a prayer and how we can interpret it in today's context, particularly in the context of contemporary issues such as the struggles of Indonesian migrant workers in Malaysia and Brunei Darussalam. An exposition of Psalm 137 can help migrant workers understand God who listens to His people who are in oppression. Psalm 137 is about how to submit all the pain, suffering, and resentment to God Himself.Abstrak. Artikel ini adalah sebuah studi Mazmur 137 dengan tujuan memberikan dasar perenungan bagi kita untuk memahami Mazmur ratapan sebagai sebuah doa dan bagaimana kita dapat memaknainya dalam konteks masa kini, secara khususnya dalam konteks isu-isu kontemporer seperti pergumulan para pekerja migran Indonesia yang berada di Malaysia dan Brunei Darussalam. Eksposisi terhadap Mazmur 137 dapat menolong para pekerja migran memahami Allah yang mau mendengarkan umat-Nya yang berada dalam penindasan. Mazmur 137 adalah tentang bagaimana menyerahkan segala kepedihan, penderitaan, sakit hati dan dendam itu kepada Allah sendiri.